2000
DOI: 10.1111/j.1469-445x.2000.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Response of the Rat Colon to the Flavonol Quercetin is Dependent on Ca2+‐Calmodulin

Abstract: The dietary flavonol quercetin induces chloride secretion in rat intestine. To clarify the underlying mechanisms, experiments were performed in Ussing chambers with tissue from rat proximal and distal colon. Quercetin induced an increase in short‐circuit current (Isc), which was largely independent of submucosal neurons, as it was not affected by the neurotoxin tetrodotoxin. The effect of quercetin was blocked by the calmodulin antagonists trifluoperazine and ophiobolin A and was diminished by a blocker of Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Quercetin increased I sc in intact distal colon tissue sheets bathed in buffer solution as previously demonstrated (Cermak et al ., 1998; 2000). A first set of experiments was carried out in order to identify the apical Cl − channels involved.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quercetin increased I sc in intact distal colon tissue sheets bathed in buffer solution as previously demonstrated (Cermak et al ., 1998; 2000). A first set of experiments was carried out in order to identify the apical Cl − channels involved.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to intact colon mucosa, both blockers failed to significantly alter the quercetin‐induced current (Figure 7b). In a previous study, we showed that Gd 3+ , a lanthanide which is able to inhibit the carbachol‐induced Ca 2+ influx into colon mucosa (Frings et al ., 1999), had no effect on the short‐circuit current induced by quercetin (Cermak et al ., 2000). In distal colon epithelium permeabilized with nystatin, the serosal addition of Gd 3+ (100 μ M ) affected neither basal I K nor the current induced by the flavonol (Figure 7a,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we show that clotrimazole, an rSK4 channel blocker (Devor et al, 1997), completely inhibited TDC-induced increase in I SC . At variance with TDC-induced Ca 2+ influx (Dharmsathaphorn et al, 1989), quercetin increases intracellular Ca 2+ concentration by mobilization from deposits (Cermak et al, 2000). Indeed, the prosecretory effect of quercetin persisted in the Ca 2+ -free buffer (which was not the case for TDC).…”
Section: Discussionmentioning
confidence: 99%